KREATIVITAS DAN INOVASI BISNIS DALAM KEWIRAUSAHAAN - jafrizal jafrizal (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2024)
This research is a literature review journal which aims to produce new and innovative ideas that can change the game, lead trends, create added value for customers, and introduce or develop new things in entrepreneurship. A literature review is carried out by collecting various literature sources that discuss the same topic, starting from books, journals, magazines that are relevant and the latest (state of art) and in accordance with those contained in the reference literature. The method used in this research is a qualitative literature review method which refers to literature review studies. The results of this research show that the role of innovation in entrepreneurship is very important to improve company performance and profits. Innovation can help companies find new ways to increase productivity, reduce costs, and improve the quality of products or services offered. In the management context, the role of creativity functions is also discussed in this research. This research can provide knowledge about innovation in the entrepreneurial process for generating new ideas that result in improvements that are highly effective and efficient in a system. So the important aspects in creativity are process and people. This research will also be related to entrepreneurial motivation in conditions that encourage, move and direct an individual's desire to carry out entrepreneurial activities, independently, believe in themselves so they can be oriented towards the future, dare to take risks, be creative and value the desire for innovation highly.